Crystallization behavior of (GeTe4)(x)(GaTe3)(100-x) glasses for far-infrared optics applications - Svoboda, Roman; Brandová, Daniela (Elsevier Science SA, 2019)
Differential scanning calorimetry (DSC), X-ray diffraction (XRD), infrared microscopy and Raman spectroscopy were used to study the crystallization behavior of the (GeTe4)(x)(GaTe3)(100-x) glasses for far-infrared optics. Two independent overlapping crystallization processes were found - the initial surface-located precipitation of hexagonal Te and Ga2Te5 phases, followed by formation of the rhombohedral GeTe phase. The initial precipitation process, and in particular the formation of the Ga2Te5 phase, was found to be catalyzed by presence of mechanically induced defects. Finely powdered materials with higher GaTe3 content also exhibited more pronounced separation of the two crystallization sub-processes. Glass stability of the prepared glasses was evaluated in terms of the Hruby criterion - the (GeTe4)(86)(GaTe3)(14) composition was found to be the most stable and most resilient to the negative crystallization-enhancing influence of structure defects. Pros and cons of the compositional evolution of the crystallization behavior (determined via full kinetic description of the involved crystallization subprocesses and kinetic prediction of the crystallization behavior) were discussed with regard to the ceramics and glass-ceramics applications. Glasses with low GaTe3 content appear to be most suitable for preparation of fully ceramic materials, whereas glasses with high GaTe3 content seem to be most suitable for the glass-ceramics applications. (C) 2018 Elsevier B.V. All rights reserved.
Krystalizační chování (GeTe4)(x)(GaTe3)(100-x) skel for dalekou infračervenou oblast aplikací
Keywords: Ge-Ga-Te glasses; Crystallization kinetics; DSC; XRD; Glass-ceramics; Ge-Ga-Te skla; krystalizační kinetika; DSC; XRD; sklokeramika